Menggugat Konsensus (Ijma') Keharaman Bunga Bank - Suparman Suparman; Suwardi Suwardi; Saini Saini (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2024)
One of the Islamic economic discourses that is often claimed to be the consensus of scholars (ijma') is the prohibition of bank interest, as evidenced by several statements and writings of contemporary Islamic economic experts. However, it is also a fact that there are many differing opinions among scholars regarding the law on bank interest. This raises several questions: Is the claim of ijma' on the prohibition of bank interest in accordance with the theory of ushul fiqh? Can it be considered ijma' when some scholars have different opinions? These questions can only be answered through an ushul fiqh approach by researching and understanding the normative study on the concept of ijma', which is extensively explained in ushul fiqh books. The conclusion derived from this study is that the ijma' on the prohibition of bank interest does not align with the principles of ushul fiqh. Therefore, it is more prudent not to dismiss the opinions of some scholars who justify bank interest. In other words, we can say that the prohibition of bank interest is the opinion of the majority of scholars, but it is not an ijma' as many people believe.